EP328/#979 Cytology and HPV DNA cervical cancer screening in HIV positive and HIV negative women. (4th December 2022) - Snyman, Leon; Richter, Karin; Lukhwareni, Azwidowi Azwidowi; Dreyer, Gerrit J; Botha, Matthys; Merwe, Frederick Van Der; Visser, Cathy; Dreyer, Greta
Abstract : Objectives: HPV-testing is becoming the preferred cervical cancer screening test. Data on HPV DNA screening in resource poor settings are limited. The objectives were to investigate cytology and primary HPV screening in women living with HIV and HIV negative women Methods: Study was performed in two academic centres in South Africa. Patients had cytology and HPV testing (Hybrid Capture-2, HC2). Those with positive tests had colposcopy and punch biopsy or loop excision of the transformation zone (LLETZ). Data were imputed using a statistical model which maintained the underlying distribution of the available results, allowing calculation for the total screening population Results: Included were 909 women with mean age 41.42 years (SD 9.82; 25–65 years). In 903 women with known HIV status, 683(75.64%) had negative cytology and 202(22.37%) had abnormal cytology. HC2 HPV was negative in 621(68.77%) women. In WLWH, 54.48% tested cytology negative compared to 79.69% in HIV negative women (p<0.0001). HC2 HPV screening had higher sensitivity (60.92%), but lower specificity (82.39%) compared to cytology (48.59% and 86.75%) for detection of CIN 2+ in all women, except in HIV negative women, where HC2 HPV specificity (75.00%) was comparable to that of cytology (79.74%). For detection of CIN3+, HC2 HPV screening had higher sensitivity (70.45%) compared to cytology (62.88%), but specificity (75.49%) was lower in whole population compared to cytology ASCUS+ (82.37). Conclusions: HC2 as screening test performs well in the whole population as well as in WLWH and HIV negative women. Cytology in WLWH is a suitable screening test in low-resource settings for this population group